2019
DOI: 10.1016/j.jor.2018.12.009
|View full text |Cite|
|
Sign up to set email alerts
|

Macroscopic observations of muscular bundles of accessory iliopsoas muscle as the cause of femoral nerve compression

Abstract: Compression of the femoral nerve (FN) to the iliac fossa has been reported as a consequence of several pathologies as well as due to the aberrant muscles. The purpose of this research was to investigate the patterns of the accessory muscles of iliopsoas muscles and the relationship of the FN in fifty semi pelvis. Accessory muscular slips from iliacus and psoas, piercing or covering the FN, were found in 19 specimens (7.9%). Based on the macroscopic structure, the muscle was categorized into two types. Pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
8
0
3
Order By: Relevance
“…Anloague and Huijbregts [ 3 ] identified bifurcated or trifurcated femoral nerves, separated by the psoas major muscle fibers at the posterior abdominal wall, that rejoined before passing behind the inguinal ligament. Variations of the femoral nerve pierced by muscular slips from the iliacus or the psoas major in the iliac fossa have also been commented on [ 4 ]. Wong et al [ 5 ] identified multi-split femoral nerve by a variant psoas quartus muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Anloague and Huijbregts [ 3 ] identified bifurcated or trifurcated femoral nerves, separated by the psoas major muscle fibers at the posterior abdominal wall, that rejoined before passing behind the inguinal ligament. Variations of the femoral nerve pierced by muscular slips from the iliacus or the psoas major in the iliac fossa have also been commented on [ 4 ]. Wong et al [ 5 ] identified multi-split femoral nerve by a variant psoas quartus muscle.…”
Section: Discussionmentioning
confidence: 99%
“…23 Muscles and fascia can be responsible for entrapping peripheral nerves. 24,25 Hypertonicity of the trapezius and neighboring neck muscles can exacerbate occipital neuralgia. OMT targeted at these regions can decrease perception of pain, relax hypertonic muscles by decreasing alpha motor neuron activity, and inhibit an active muscle's contraction (by increasing tension on the Golgi organ complex).…”
Section: Occipital Neuralgia and Tinnitus Pathophysiologymentioning
confidence: 99%
“…Прямую корреляционную связь при данном патологическом процессе можно объяснить особенностью иннервации ППМ. При блоке бедренного нерва тонус ППМ сохраняется за счет ветвей поясничного сплетения [7].…”
Section: результатыunclassified
“…Высокая корреляционная связь, отражающая зависимость проявлений нейропатии бедренного нерва от выраженности тонуса подвздошнопоясничной мышцы (ППМ) Fig. 1 ППМ на развитие компрессионно-ишемической нейропатии бедренного нерва при относительно сохранной иннервации самой ППМ, что не противоречит данным литературы [7]. Высокая обратная корреляционная взаимосвязь компрессии бедренного нерва и выраженности болевого синдрома в области тазобедренного сустава и передней поверхности бедра позволила сделать вывод о влиянии туннельной нейро патии бедренного нерва на развитие болевых ощущений и дегенеративных изменений в тазобедренном суставе.…”
Section: заключениеunclassified
See 1 more Smart Citation